COUNTERING ILLEGAL EMPLOYMENT IN THE RUSSIAN FEDERATION: IMPACT ON THE STATE OF THE LABOR MARKET - MIRONOVA S.M; LITVINENKO Z.G. (Legal Bulletin)
Currently, with the expansion of employment types, the issue of distinguishing illegal informal employment, defining their characteristics and methods of combating them is becoming relevant. Federal Law No. 565-FZ «On Employment of the Population in the Russian Federation» reflects issues of combating illegal employment in Russia, which is expressed in the consolidation of general rules for the organization and work of regional interdepartmental commissions to combat illegal employment, their interaction with other government bodies, including tax authorities. It is not clear whether illegally employed and informally employed are synonyms or are different categories. In this regard, it is of interest to study the issue of the very concept of illegal employment, combating illegal employment, legal regulation of this issue, as well as the practice of current implementation at the regional level. The materials of the study were regulatory legal acts, statistical data of the Russian Federation, Russian scientific research. The comparative legal method, methods of formal logic (analysis, synthesis, generalization, induction, deduction, etc.) were chosen as the main research methods. Recently , the concept of employment as a whole has been changing, new types of employment have appeared, for example, platform employment, self-employment, which inevitably affects the change in the labor market. At the same time, the emergence of such types of employment that are atypical for the earlier period predetermines, on the one hand, a revision of the concepts of «illegal employment», «informal employment», on the other hand, the need to organize measures to combat illegal employment in the regions, which requires the creation of appropriate interdepartmental commissions. At the same time, based on the very concept of «illegal employment», enshrined in the law on employment, in fact, we are talking about identifying cases of substitution of labor relations for other types of employment. At the same time, the emergence of platform employment, which in its characteristics differs in part from labor relations, necessitates the normative consolidation of the characteristics of such employment, which requires the earliest possible adoption of a federal law on platform employment in Russia.